Strategies for recruitment of relatives of BRCA mutation carriers to a genetic testing program in the Bahamas. (6th September 2014) - Trottier, M.; Lunn, J.; Butler, R.; Curling, D.; Turnquest, T.; Royer, R.; Akbari, M.R.; Donenberg, T.; Hurley, J.; Narod, S.A.
<x xml:space="preserve">Abstract</x> The prevalence of BRCA1 and BRCA2 mutations among unselected breast cancer patients in the Bahamas is 23%. It is beneficial to advise relatives of mutation carriers that they are candidates for genetic testing. Women who test positive are then eligible for preventive interventions, such as oophorectomy. It is not clear how often relatives of women with a mutation in the Bahamas wish to undergo genetic testing for the family mutation. Furthermore, it is not clear how best to communicate this sensitive information to relatives in order to maximize patient compliance. We offered genetic testing to 202 first‐degree relatives of 58 mutation carriers. Of 159 women who were contacted by the proband or other family member, only 14 made an appointment for genetic testing (9%). In contrast, among 32 relatives who were contacted directly by the genetic counselor, 27 came for an appointment (84%). This study suggests that for recruitment of relatives in the Bahamas, direct contact by counselor is preferable to using the proband as an intermediary.